Pelatihan Dunia Usaha Berbasis Teknologi untuk Meningkatkan Daya Saing PT Salam Sejahtera - Tamara Rahma Widowati; Dian Julianto Wahyudi; Chintia Dwi Wangsa Kuswardani; Danang Yugo Pratomo; Saifuddin Karim; Yayi Febdia Pradani; Imam Muhtarom; Nikmatus Sholikha (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
ABSTRACT In the digital era, adopting technology in business is crucial to enhance competitiveness, especially for SMEs in the tourism sector. PT Salam Sejahtera faces challenges in digital technology adoption, particularly in marketing and operational efficiency. This community service program aims to improve workers’ digital literacy through technology-based training. The methods include material introduction, technology demonstrations, hands-on practice, discussions, and result evaluations. The training equips participants with digital marketing skills, online booking management, and Customer Relationship Management (CRM) implementation. The results indicate an improvement in digital understanding, operational efficiency, and business competitiveness. This training demonstrates that digital transformation enhances business effectiveness and expands market reach. Continuous implementation is expected to support SMEs’ adaptation to digitalization. Keywords: Digitalization; Training; Digital Marketing; Operational Efficiency